Retained Fetal Bones in the Uterus Emerging as the Cause of Suicide: A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
Retained fetal bones in the uterus post abortion may result in long-standing unexplained secondary infertility. We report a case of suicide of a 33-year-old woman by self-immolation. Pieces of retained fetal bones and cartilages were found unexpectedly at autopsy in the uterine cavity. The bones had been retained in the uterus for 4 years after an elective abortion. Since then she had been unable to conceive and was being treated for secondary infertility. The distress caused by the infertility lead her to commit suicide. We have discussed the incidence, aetiology, pathology and complications of this rare cause of infertility.
Keywords: Forensic medicine; Forensic pathology; Fetal bones; Retention; Secondary infertility; Suicide